Implementasi High Performance Computing Cluster Menggunakan Rocks Cluster - Richie R. Tokan; Mochammad Hannats Hanafi Ichsan; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Rocks Cluster is a linux distribution that is devoted to building a High Performance Cluster Computing by connecting several personal computers which are then called nodes. Cluster performance is measured by looking at the system's ability to process floating point numbers by using the LINPACK benchmark library and the OpenBLAS arithmetic library. In this study also used SLURM (Simple Linux Utility for Resource Management) to run an interactive job on the cluster by adjusting the resource requirements of the cluster to run the task. From the benchmark test results obtained a value of 15.0323 GigaFlops within 692.35 seconds or about 11.5 minutes on testing with 25000 matrix. For the results of interactive jobs testing using SLURM, the system shows efficient performance for the use of system resources for workload, cpu, memory and network ussage.